PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI EKONOMI DISERTAI KEKERASAN - Rikardo Horas Uli Tua Simanjuntak; Ida Hanifah (JURNAL DOKTRIN REVIEW, 2023)
Children must be protected from all forms of cruelty and oppression, in any form, even though there are already a set of regulations that protect children from the dangers of economic exploitation, and the problem of economic exploitation of children from year to year experiences very complex developments, so that child exploitation increases every year. annually indicates that there are significant obstacles that occur at the level of implementation. The discussion in this study is to analyze the factors that cause economic exploitation accompanied by violence against children, and criminal law policies in tackling child exploitation and as well as legal protection for child victims of economic exploitation accompanied by violence. This type of research is normative legal research. Based on the results of this study, it is concluded that the background that makes children victims of trafficking in persons is due to the motive of poverty, and difficulty finding work, education, law enforcement against perpetrators of child exploitation crimes must be implemented strictly and indiscriminately, by implementing statutory regulations - promulgation along with the application of serious criminal threats is one step to be able to provide a deterrent effect for the perpetrators